FACTORS AFFECTING DIVIDEND PAYMENT POLICY - Seto Sulaksono Adi Wibowo; Agung Bana (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
Dividend payments are a routine activity that is usually done by the company once a year. Before dividend payments are made many factors are considered before the company pays the dividends. This study aims to determine what factors affect the payment of dividends. The sample used in this study is all non-financial sector companies that pay dividends for 3 consecutive years 2016 to 2018. This study uses the Eviews test tool and uses multiple regression tests. The results of this study indicate that profitability, life cycle and company size have positive effects while liquidity, cash flow, growth opportunities and leverage have no effect on dividend payout policies.